ALUMINUM-CHLORIDE CATALYZED REGIOSELECTIVE ALLYLSILYLATION OF ALKENES - CONVENIENT ROUTE TO 5-SILYL-1-ALKENES - YEON, SH; LEE, BW; YOO, BR; SUK, MY; JUNG, IN (AMER CHEMICAL SOC, 1995)
Allyltriorganosilanes react regioselectively with terminal or cyclic alkenes in the presence of aluminum chloride catalyst under mild conditions to afford 5-silyl-1-alkenes in good yield. In the allylsilylation of terminal alkenes the silyl group adds to the terminal carbon and the allyl group to the inner carbon of the double bond and the reaction with cyclic olefins gives allylsilylated products having the silyl and allyl groups in the trans position. This allylsilylation is a convenient route to 5-silyl-1-alkenes. In the allylsilylations with the stereohomogeneous (Z)-crotyltrimethylsilane, an allylic inversion is observed indicating a stepwise process of allylsilylation.